From Sites to Landscapes: How Computing Technology Is Shaping Archaeological Practice. - Ch'ng, Eugene; Chapman, Henry; Gaffney, Vincent; Murgatroyd, Phil; Gaffney, Chris; Neubauer, Wolfgang (Computer (00189162), 2011)
Remote sensing, powerful computing engines, and agent-based models offer new ways to interpret data and broaden data collection, moving archaeologists closer to their ultimate goal of approximating the individual within an extensive, interpreted, digital environment. The first Web extra is a video that demonstrates how the advanced acquisition and processing of magnetic data has led to new discoveries and insights, such as the "Henge" monument excavated near Stonehenge in 2010. The second Web extra is a video that illustrates how researchers used 3D seismic data, initially collected for use in oil and gas exploration, to reconstruct Doggerland, a lost Mesolithic landscape that was inundated by the North Sea during the last great period of global warming.